The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7150/thno.36045
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA PiHL regulates p53 protein stability through GRWD1/RPL11/MDM2 axis in colorectal cancer

Abstract: We identified a novel long noncoding RNA (lncRNA) upregulated in colorectal cancer (CRC). We elucidated its role and clinical significance in CRC carcinogenesis.Methods: LncRNA candidates were identified using TCGA database. LncRNA expression profiles were studied by qRT-PCR and microarray in paired tumor and normal tissues. The independence of the signature in survival prediction was evaluated by multivariable Cox regression analysis. The mechanisms of lncRNA function and regulation in CRC were examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…These regulatory functions of lncRNAs influence the mRNA expression of the target genes, consequently modulating their protein expression levels. Moreover, lncRNAs are able to affect protein expression level independently, without influencing the mRNA expression level, by predominantly regulating mRNA translation and protein stability [14,15]. In the present study, we identified that the lncRNA RP11-284P20.2 interacts with c-met mRNA via complementary base pairing, and also found that RP11-284P20.2 binds to EIF3b protein with high affinity.…”
Section: Discussionsupporting
confidence: 52%
“…These regulatory functions of lncRNAs influence the mRNA expression of the target genes, consequently modulating their protein expression levels. Moreover, lncRNAs are able to affect protein expression level independently, without influencing the mRNA expression level, by predominantly regulating mRNA translation and protein stability [14,15]. In the present study, we identified that the lncRNA RP11-284P20.2 interacts with c-met mRNA via complementary base pairing, and also found that RP11-284P20.2 binds to EIF3b protein with high affinity.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, a coimmunoprecipitation assay revealed that DJ-1 does not directly interact with p53 in CRC. An oncogene signaling pathway has been found to contribute to apoptosis by targeting MDM2 and indirectly activating the p53 pathway (36)(37). Therefore, the current study explored whether activation of the MDM2/ p53 pathway mediated the oncogenic effects of DJ-1 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is frequently inactivated or lowly expressed in human cancer, and it is able to directly bind to gene promoters to promote or inhibit gene expression ( Vousden and Prives, 2009 ). Currently, numerous lncRNAs are identified as the targets of p53, such as uc061hsf.1 ( Yao et al, 2020 ), PiHL ( Deng et al, 2020 ), and TRMP ( Yang et al, 2018 ). Herein, two p53 binding motifs on ST8SIA6-AS1 promoter were predicted using in silico analysis, and we performed ChIP and luciferase reporter assays and found that p53 could bind to the motif away from the transcription initiation site, inhibiting ST8SIA6-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%